Generative Design Integrated with the Show of Contemporary Dance Glow - Eloise Shimoda, Karen; Belluzzo de Campos, Gisela (DAT Journal, 2021)
This article addresses concepts related to contemporary dance and the fusion of language with generative design. He gives a brief account of contemporary dance, focusing on the way professionals have experimented with technologies and other languages integrated into their choreographic projects. It addresses the use of generative design and algorithms, as part of the creation process in the show Glow, in which the designer manipulates and explores the use of graphic forms, obtaining unexpected and complex results through a flexible structure that adapts to the video projection and motion capture. The methodological approach is qualitative with a cultural and historical bias, complemented by observation and study of the creative and technical process, in graphic materials, texts, exclusive videos and images. Finally, a description of the show is made, paying attention to the use of graphic elements as extensions of the choreographic movement.